2013
DOI: 10.1111/tmi.12095
|View full text |Cite
|
Sign up to set email alerts
|

Serum CCL11 (eotaxin‐1) and CCL17 (TARC) are serological indicators of multiple helminth infections and are driven by Schistosoma mansoni infection in humans

Abstract: Abstractobjectives To evaluate systemic serum cytokine and chemokine markers for inflammation and Th1/ Th2 responses in relation to multiple helminth infections, parasite burden and/or nutritional status of individuals.methods In a longitudinal study, stool samples from 210 individuals from an area highly endemic for Ascaris lumbricoides, Necator americanus and Schistosoma mansoni were examined before and 12 months after clearance of parasites by chemotherapy. On both occasions, the presence of monoor multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
4
14
1
Order By: Relevance
“…Furthermore, the expression levels of the chemokines CCL17 and CCL22 were positively correlated with the HBV DNA load. This finding was also consistent with those of previous reports 35,36 . However, a previous study reported that the frequency of Th17 cells and the levels of IL‐17 increased with the mitigation of liver inflammation and the decline in HBV DNA load and that the Treg/Th17 ratio decreased 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the expression levels of the chemokines CCL17 and CCL22 were positively correlated with the HBV DNA load. This finding was also consistent with those of previous reports 35,36 . However, a previous study reported that the frequency of Th17 cells and the levels of IL‐17 increased with the mitigation of liver inflammation and the decline in HBV DNA load and that the Treg/Th17 ratio decreased 37 .…”
Section: Discussionsupporting
confidence: 92%
“…Dawson et al (2009) reported significant higher CCL17 expression on day 7 PI in liver tissue of pigs given retinoic acid and infected with A. suum than in uninfected controls; however, to our knowledge, a significant upregulation due to A. suum infection alone has not previously been demonstrated for this chemokine. In agreement with our results, Geiger et al (2013) found infection with helminths was associated with higher CCL17 concentration in human serum and Burke et al (2011) reported higher CCL17 expression in lungs of Schistosoma japonicum-infected mice compared with uninfected controls.…”
Section: Disscussionsupporting
confidence: 82%
“…This correlates with the earlier findings from Geiger et al . [31], who showed elevated levels of CCL11 in serum samples of egg + individuals from Brazil. This group, however, found no differences in CXCL10 levels, whereas our data showed significantly lower levels of this chemokine in egg + individuals when compared to both other groups, and was significantly associated with an uninfected state in our expanded regression analyses (Supporting information, Table S2).…”
Section: Discussionmentioning
confidence: 99%